Bronchoscopic survillance during early postoperative period after lung transplantation - R., Jackin Moses; R., Anantharaman; Cherian, Kottoorathu Mammen; S., Mohamed Thayub; R., Raj Ganesh (International Journal of Research in Medical Sciences, 2019)
Background: Lung transplant has become an accepted modality of treatment of patients with end stage pulmonary disease, establishing protocols for improving survival in these patients is the need of the hour. The aim of this study was to assess the use of bronchoscopic surveillance during early post-operative period after lung transplantation. Methods: It is a hospital based retrospective study; the study was carried out in a lung transplant centre located in Chennai, India. A total of eight cases of single lung transplantation were done during the period of one year. Six patients were selected based on the inclusion criteria and the use of bronchoscopy during the immediate post-operative period followed by bronchoscopy during the early hours of everyday for the first week and the success in reduction of immediate post-operative infection and observations has been analysed. Results: In analysis of all the six cases, the positive signs of early morning bronchoscopy done were identified, mucus plugs which contribute to significant hypoxemia and morbidity were not observed in any of the patients. New patch was also not observed in any of these patients. Culture positivity from the donor lung carrying over to the recipient was observed in just one of these patients. Conclusions: This protocol based frequent bronchoscopy prevents ‘Surprise’ patches in the lungs. Performance of Broncho Alveolar Lavage on a regular basis avoided the possibility of infections developing by early screening and aided as a tool for identification of acute neo lung rejection.